KAJIAN TINGKAT PARTISIPASI, TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN DANA OTONOMI KHUSUS PAPUA BERDASARKAN TIPOLOGI WILAYAH - Mesak Iek (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2014)
Objective of the Study is to identify planning and financial management problem which are sourced from Papua's Special Autonomy Fund for education and health services in mountainous areas, difficult access areas and easy access areas. The approach used in this study is a case study which is one of the qualitative research approaches using inductive logic process. The scope of the study area is divided into three regions, namely easy access plains, coastal lowlands and difficult access, and mountains. Samples were taken according to the typology of district areas, namely: (a) the mountainous region : Jayawijaya, Tolikara, and Mountains, (b) difficult  access of coastal areas: Asmat regency, Yapen Islands, Keerom, (c) easy access plains areas : District Supiori, Merauke and Jayapura. Furthermore, 1 district and 2 villages were taken from each district. The samples were taken from each district in accordance with the studies that may represent the locus of social organization, executives and legislative those are SKPD and hospitals. While for the sample of villages/urban population were taken representatively from elementary school, junior high school and Health Center. And for the study of individual locus that represent the population are teachers, doctors, health workers, traditional leaders, religious leaders, and households are all Papuans so that the sample in this study amounted to 598 people. In this case, statistical descriptive analysis tool is used. This study found that the Management which is not optimal in 3 areas are Reporting and Internal Control. Activities funded by the special autonomy fund did not inform freely to the public. During this time the local government did not involve teachers, medical personnel and Papua native communities to do the planning, implementation and monitoring of spending special autonomy funds. During these activities are carried out by SKPD which is financed by the special autonomy funds are not openly communicated to all those in need: easy access areas, difficult access areas, and mountainous areas. At the planning stage, programs and activities funded by Autonomy funds are not transparent. The only real activity that is known by society is Respek (villages’ strategic planning development). Many activities where the source of activity and funds are still unknown by teachers, medical personnel, and the public. According to the society (sample), the management of special autonomy funds is not accountable. The local government is necessary to disseminate the activities that use special autonomy funds, as well as formal and informal information to the public about the activities that used special autonomy funds. All stakeholders need to be involved to participate in the management system of special autonomy fund. Musrembang format that has been carried out needs to be done properly.Keyword : Participation, Transparency, Accountability, Special Autonomy Funds